Case report: Restoration of an open 12 cm femoral defect treated with the Masquelet technique in a 20-year-old polytrauma - George D. Chloros (Elsevier, 2021)
Infected post-traumatic femoral defects are challenging to treat, and limited options exist. The case of a 20-year-old polytrauma male who sustained a segmental femur fracture involving the femoral neck, distal femur and an intermediate diaphyseal bone defect of 12 cm is presented. The patient declined a long-term frame in his femur. The 2-stage Masquelet procedure resulted in successful outcome with limb preservation.